Exile Materialities and Their Brushstrokes of Colour - Rivera, Francisco (Anthropologica, 2022)
Urban odonyms and public art that refer to the Chilean dictatorship (1973–1990) are artifacts within the cultural landscapes of Toronto, Laval, and Montreal. As commemorative material devices, I suggest odonyms and public art offer a symbolic way to cope with the experience of exile. Furthermore, these artifacts create social relations between Chilean exiles and Canadian urban spaces that contribute to forming a foreign community and define their present and future. Using a series of photographs, I chronicle the memorialization in Canada of a traumatic period in recent Chilean history.